The Role Of Government Spending In Education Inequality: Evidence From Indonesia With A Panel Data Analysis - Setyadi, Sugeng (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to determine the level of inequality in education as measured by the Gini Education Coefficient (KGP) in Indonesia, to compare the level of inequality between provinces and to analyze the factors that influence educational inequality between provinces in Indonesia. This research was conducted in a number of Indonesian provinces in 2017-2019 using a panel data anayisis methods. The results showed that education inequality in Indonesia in 2017-2019 was in the low inequality category. The number of Gini coefficients is getting smaller each year, which indicates a more even distribution of education in Indonesia. When viewed from the regional classification, Eastern Indonesia has a higher KGP score than the Western part of Indonesia. The education budget has a negative and significant effect on education inequality in Indonesia in 2017-209 while the number of teachers and school principals has a significant positive effect on education inequality in Indonesia in 2017-2019.